Trend Analysis of Sesame Production in Arid Rajasthan - Ram, K Anantha; Dave, B K (Annals of Arid Zone, 2016)
Sesame production trends, problems and prospects in Rajasthan (India) were examined by analysing the secondary data. The problem of decreasing sesame production is traced to decreasing area allocation to the crop. The low yields of local varieties in the absence of viable new technology have tended to take away the area normally used to be allocated to this crop, in the favour of pulses.